2012
DOI: 10.1177/0194599812446903
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea in Children with Laryngomalacia

Abstract: Laryngomalacia may contribute significantly to OSAS in some children who are 12 months and older. Sleep endoscopy appears to be an effective method in the diagnosis of SDL. When present, a supraglottoplasty can be an effective procedure and may significantly improve symptoms of OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…In a surgical series of children older than 1 year with both SDB and LM by Digoy et al, 5 there was a statistically significant improvement in apnea-hypopnea index and minimum oxygen saturation on PSG following supraglottoplasty as well as subjective symptom improvement in the majority of children.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a surgical series of children older than 1 year with both SDB and LM by Digoy et al, 5 there was a statistically significant improvement in apnea-hypopnea index and minimum oxygen saturation on PSG following supraglottoplasty as well as subjective symptom improvement in the majority of children.…”
Section: Discussionmentioning
confidence: 89%
“…[4][5][6][7][8][9] Researchers have also proposed that LM may be state dependent, manifesting only during sleep or precipitated by exercise. 7,[10][11][12][13] Concomitantly, some series have gone on to report the success of supraglottoplasty in alleviating symptoms in these atypical situations 4,5,8,9 We have noticed that large series reporting presenting features have focused on classic LM and excluded older children and atypical presentations. 14,15 Therefore, to our knowledge, there are no large studies that document the distribution of these presentations and the characteristics of these subgroups within a large population of children diagnosed as having LM.…”
mentioning
confidence: 99%
“…There are several features of DS that may increase risk for sleep-disordered breathing including decreased pharyngeal muscle tone, retroglossia, macroglossia, midfacial hypoplasia, lymphoid hyperplasia, and high BMI [6]. Commonly identified sites of obstruction include the lingual tonsils, tongue base and the supraglottis, none of which can be seen on direct physical exam, but all of which can be corrected surgically [1920].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analysis showed that for patients with laryngomalacia, there was no significant difference in effect if the surgery was performed as a primary intervention or secondarily after another type of airway surgery, such as AT [ 51 ]. Digoy et al reported postoperative coughing and dysphagia [ 52 ]. These studies suggest that supraglottoplasty is an effective treatment for patients with underlying laryngomalacia, although it is still not 100% effective [ 51 ].…”
Section: Surgical Proceduresmentioning
confidence: 99%